Advances in Research on Age in the Workplace and Retirement - Hannes Zacher (Frontiers Research Topics, 2018)
Shifts in the age composition of the workforce coupled with dynamic definitions of retirement represent important issues that influence work processes and, more generally, the experience of working across one's career. For example, redefinitions of careers and the changing nature of working have contributed to the emergence of distinct forms and patterns of work experiences across the prototypical work lifespan. Likewise, older individuals are increasingly delaying retirement in favor of longer-term labor force participation. The study of age and work, and work and retirement by industrial, work, and organizational (IWO) psychologists and scholars of human resources management and organizational behavior (HR/OB) has recently proliferated in part as a result of such trends, along with the recognition that age-related processes are important indicators of various proximal (e.g., job attitudes, work behaviors, work motives, and wellbeing) and distal outcomes (e.g., sustainable employability, climates for aging, and firm performance) at various levels of abstraction in modern work environments. Recent theoretical advances have suggested that age, along with individual psychological factors and various contextual influences can jointly influence work outcomes that contribute to long-term employment success, including work performance, job attitudes, work orientations, and motivations. Similar theoretical developments concerning retirement have postulated individual and contextual elements that drive success in the transition from career and work roles to non-work and leisure as well as post-retirement bridge employment roles. In this Research Topic, we aim to curate a collection of papers that are representative of current trends and advances in thinking about and investigating the role of age in workplace processes and the changing nature of retirement. Our hope is to showcase various contemporary ideas and rigorous empirical studies as a means to inform broader thinking and to support enhanced theorizing and organizational practice regarding these processes.